Implementation of community dental and oral health care before COVID-19 pandemic to new normal period at Public Health Care - Muhamad Tio Dwi Hertanto; Wahyu Hidayat; Netty Suryanti (Padjadjaran Journal of Dentistry, 2022)
ABSTRACT